Teaching and the case method text, cases and readings - Barnes, Louis B. (Harvard Business School Press, 1994)
"This third edition of Teaching and the Case Method is a further response to increased national and international interest in teaching, teachers, and learning, as well as the pressing need to enhance instructional effectiveness in the widest possible variety of settings. Like its predecessors, this edition celebrates the joys of teaching and learning at their best and emphasizes the reciprocal exchange of wisdom that teachers and students can experience. It is based on the belief that teaching is not purely a matter of inborn talent. On the contrary, the knowledge, skills, and attitudes that make for excellence in teaching can be analyzed, abstracted, and learned. One key premise of Teaching and the Case Method is that all teaching and learning involve a core of universally applicable principles that can be discerned and absorbed through the study and discussion of cases."--BOOK JACKET